(untitled) (Journal of Information Technologies in Education (ITE), 2010)
In article the method of preparation for passing licence examination "Pharmacy" at studying of chemical disciplines on first three courses. Connection of the school program with the program of higher educational medical institutions. The organisation of arrangement on revealing of risk group among students is considered. Comparative results according to the licence integrated examination "Pharmacy" from 2007/09 educational years are given.